Synthetic Curcumin Analogues Present Antiflavivirus Activity In Vitro with Potential Multiflavivirus Activity from a Thiazolylhydrazone Moiety - Mateus Sá Magalhães Serafim; Thales Kronenberger; Renata Barbosa de Oliveira; Erna Geessien Kroon; Jônatas Santos Abrahão; Bruno Eduardo Fernandes Mota; Vinícius Gonçalves Maltarollo (MDPI AG, 2023)
Arboviral diseases caused by flaviviruses, such as dengue, are a continuing threat and major concern worldwide, with over three billion people estimated to be living with the risk of dengue virus (DENV) infections. There are thus far no antiviral drugs available for treatment, and limited or no vaccines are available. Curcumin and seven synthetic analogues were evaluated for their antiviral activity against dengue virus serotype 2, yellow fever virus and Zika virus, as well as for their cytotoxicity in Vero cells, both by employing MTT assays. Compounds 6 and 7, which present a thiazolylhydrazone moiety, showed moderate activity against all three flaviviruses, with selectivity index (SI) values up to 4.45. In addition, the envelope protein (E) was predicted as the potential target inhibited by both compounds, supported by molecular docking and dynamics simulation analysis. We hope that this data can contribute to the development of new curcumin antiviral analogues in the near future and can help in the search for new promising compounds as potential therapeutic agents to treat flaviviruses infections.